PLAGIARISM IN THE INDONESIAN HIGHER EDUCATION: A STUDY OF NON-ENGLISH MAJOR UNDERGRADUATES - Dang Arif Hartono; Stefanus Angga Badara Prima (STKIP Siliwangi, 2023)
This study aims to investigate the prevalence of plagiarism among university students and identify the specific types of plagiarism that are most commonly committed in their written work. To examine the extent of plagiarism among university students, the present study employed a textual analysis approach and utilized the iThenticate, a professional and subscription-based plagiarism checker. A sample of 39 participants, all students from an intact class, were recruited for the study and they each independently composed argumentative essays. The essays were subjected to analysis using iThenticate to determine the prevalence of plagiarized content and manual analysis was subsequently performed to validate the results obtained from iThenticate and classify the types of plagiarism present in the essays. The results reveal that the students' essays contained a relatively low level of plagiarized content, comprising only 9.87% of the total text. The most prevalent form of plagiarism detected was mosaic plagiarism, with 39 cases identified. This was followed by verbatim plagiarism, with 16 cases identified. The findings of this research suggest that the students may have difficulty dealing with mosaic plagiarism and may require comprehensive training on proper paraphrasing techniques.